قطع الكبد الجراحي للنقائل الورمية السرطانية من غير سرطانات القولون و المستقيم - أيوب, عماد (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة 10 مرضى بنسبة 70% للإناث ومتوسط الأعمار 47.1 سنة. لقد توضع الورم البدئي في الثدي في 40% وفي المبيض في 20% و كان ساركوما عضلية في 20% و كل من الكلية و المعدة بنسبة 10%. تم تشخيص وجود النقيلة او النقائل الكبدية بشكل متزامن مع تشخيص الورم البدئي في حالتين و بنسبة 20% بينما تم حدوث النقائل الكبدية بشكل متأخر في 80% من الحالات. وجدت النقيلة الوحيدة عند 80% بينما شكلت النقائل المتعددة نسبة 20%. و كان قطر النقيلة اقل من 5 سم في 5 حالات و بنسبة 50% و كانت اكبر او يساوي 5 سم في 50% من الحالات. شكل قطع الكبد لقطعة او قطعتين او 3 قطع كبدية الاجراء الجراحي الاكثر تواترا و بنسبة 70% من الحالات في حين تم اجراء قطع فص كبدي ايمن تام في حالة واحدة. حدث تجمع صفراوي تالي للجراحة في حالة واحدة و لم تستدعي التداخل الجراحي. و حدث التجمع الصفراوي (البيليوم) في حالة واحدة وحدث الناسور الصفراوي في حالتين و لم تحدث أية وفاة خلال الاشهر الثلاثة الاولى التالية للجراحة. معدل البقيا للسنة الاولى كانت بنسبة 100% اما البقيا لمدة 3 سنوات كانت 70% و بين 3 الى 5 سنوات فكانت 40% و في حالة واحدة تجاوزت البقيا 5 سنوات The study included 10 patients with70% of females and average age of 47,1 years. The primary tumor was located in the Breast at 40% and in Ovar at 20% and Sarcomas at 20% and 10% in Kidney and 10% in Gastric. in 2 cases (20%) was the livermetastases as a synchron with the main tumor while the metachron metastases was in 80% of cases. The single metastases was found at 80% while the multiple metastases accounted for 20%. The transfusion diameter was less than 5 cm in 5 cases and 50% and it was larger or equal to 5 cm in 50% of all the cases. The most common surgical procedure was segment (1 or 2 or 3 segments) resection in 70% of all the cases. The hemi hepatectomy was in one cases, 10%. None of the patients had any complications which requiring a reoperation. Bilioma occurred in one case and Biliary fistula occurred in two cases. The survival time for the first year was 100% and 70% for (3) years and 40% for (3-5) years and in one case till now mor than 5 years.